Pengaruh Self Regulated Learning Dan Lingkungan Teman Sebaya Terhadap Hasil Belajar Mata Pelajaran Fikih Kelas Xi Putri Ma Tarbiyatut Tholabah Kranji Paciran Lamongan - Tsani Mazro’atur Rohmah; Anang Romli; Raikhan (Darajat: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study was to determine: 1) students' self-regulated learning (SRL) 2) Students' peer environment 3) student learning outcomes 4) the effect of SRL on student learning outcomes 5) the influence of peer environment on student learning outcomes 6) the influence of SRL and peer environment on student learning outcomes. This study uses quantitative methods, data collection instruments using questionnaires and documentation. This research was conducted at MA Tarbiyatut Tholabah Kranji Paciran Lamongan. Respondents in this study amounted to 59 students. The independent variables of this study were SRL and peer environment, while the dependent variable was learning outcomes. The results of this study indicate that: 1) SRL Students are classified as good. This is evidenced by the results of descriptive analysis which states that the mean > mode (77.71>73). 2) The peer environment of students is quite good. This is evidenced by the value of the results of the descriptive analysis mean > mode (76.42>70). 3) Student learning outcomes are classified as Complete. This can be proven from the results of descriptive statistical analysis Mean > KKM (86.00> 70). 4) there is no significant effect of SRL on learning outcomes. This is evidenced by the value of t count < t table (1.074 < 1.672) and the value of sig. P-value is 0.287 > 0.05. The percentage of the influence of SRL on student learning outcomes is 2%. 5) There is a significant influence of peer environment on learning outcomes. This is evidenced by the value of t count > t tabel (4.267 > 1.672), and the value of sig. P-value is 0.000<0.05. The percentage of peer environment influence on learning outcomes is 24.2%. 6) There is a significant effect of SRL and peer environment on learning outcomes. This is evidenced by the value of F count > F tabel (9.183>3.16), and the value of Sig. or P-Value < 0.05 (0.000<0.05). The percentage of the influence of SRL and peer environment on student learning outcomes is 24.7%, while the remaining 75.3% is determined by other variables outside the study.